Climatic gradients within temperate Europe and small-scale species composition of lichen-rich dry acidophilous Scots pine forests. (April 2015) - Košuthová, Alica; Svitková, Ivana; Pišút, Ivan; Senko, Dušan; Valachovič, Milan; Zaniewski, Piotr Tomasz; Hájek, Michal
Abstract: We investigated patterns in community composition in Central-European lichen-rich pine forests along a macroclimatic gradient, using two plot sizes. Diversity of lichens, especially the number of boreal and subatlantic taxa per plot increased from southern Slovakia to northern Poland (Baltic Sea). The ecological indicator value for continentality was highest in two inland regions which were characterised by low winter temperatures. Principal coordinates analysis sorted the regions along two major compositional gradients of similar importance, one mirroring the south-to-north gradient and correlating with the Gorczyński index of thermal continentality, and a second correlating with lowest winter temperature. Regional differences driven by macroclimate were the most important determinant of species composition even in small plots. Continentality was of primary importance in assembling terrestrial lichen communities, but its particular components acted differently. Lowest winter temperature appeared to be well connected with ecological meaning of continentality, which is expressed among others in ecological indicator values.